Diffusing the Diabetes Bomb: A Study on the Risk of Diabetes among the Youth in Kerala using the Indian Diabetes Risk Score - Megha V; Merin Jose; Neha S; Shaliet Rose Sebastian (Indian Journal of Health Sciences and Biomedical Research KLEU, 2026)
Background: Despite being a relatively small state, Kerala has a high prevalence of diabetes in India, with approx. 16% of the population affected. A worrying proportion of cases remain undiagnosed, putting individuals at risk of complications without proper management. Early diagnosis, effective management, and addressing risk factors are crucial to controlling the disease and its complications. Objective: To assess the risk of diabetes and its correlates among youth of both gender belonging to age group of 20–35 years using the Indian diabetes risk score in Thiruvalla, Central Kerala.Methodology: A cross sectional study was conducted among youth of both gender belonging to age group of 20–35 years from June 2023 to December 2023. The data was analyzed using the IBM statistical package for social sciences version 20. The results have been presented as tables and charts showing percentages. Chi-square test and odds ratio were used for analyzing the association between demographic variables and diabetes risk among the study participants.Results: Majority of the youth in the study were under a moderate risk of getting Diabetes (74%). While physical activity was found to be protective against the risk of Diabetes, Family history of Diabetes, Stress and Abdominal Obesity were found to be risk factors for Diabetic risk among the study participants.Conclusion: The study findings underscore the need for increasing the awareness among the youth regarding the impending Diabetes epidemic.